From Chalkboard to Dashboard: Leveraging Real-Time Analytics for Evidence-Based Education Management in Rural Schools - Yance Manoppo; Leny Sopia Latuny (Journal of Paddisengeng Technology, 2025)
Background. The growing demand for evidence-based decision-making in education highlights the importance of real-time data in guiding school management practices. Rural schools, however, often face unique challenges such as limited access to resources, inadequate infrastructure, and insufficient monitoring systems, making it difficult for administrators and teachers to evaluate progress effectively. Transitioning from traditional chalkboard practices to data-driven dashboards provides opportunities to address these challenges by leveraging analytics to improve educational outcomes and equity. Purpose. This study aimed to examine how real-time analytics can be integrated into rural school management to support evidence-based decision-making. Specifically, it explored the potential of dashboard systems to enhance monitoring of student performance, teacher effectiveness, and resource allocation in under-resourced contexts. Method. The research adopted a mixed-method design involving 15 rural schools. Quantitative data were collected through digital dashboards tracking attendance, assessment scores, and teacher engagement, while qualitative insights were obtained from interviews with school leaders and educators. Data were analyzed using descriptive statistics and thematic coding. Results. Findings indicate that dashboards significantly improved administrators’ ability to identify learning gaps, monitor teacher performance, and allocate resources more effectively. Teachers reported greater confidence in instructional planning when provided with real-time feedback. However, challenges such as internet connectivity and digital literacy remained barriers. Conclusion. The study underscores the transformative potential of dashboards in rural education. By embracing real-time analytics, schools can shift towards a culture of evidence-based management that fosters accountability, inclusivity, and improved learning outcomes.